PERCONTOHAN RUANG KOMUNAL DI RUMAH SUSUN TAMBORA, JAKARTA BARAT - Maria Immaculata Ririk Winandari; Julindiani Iskandar; Dedes Nur Gandarum; Sri Handjajanti (Universitas Trisakti, 2020)
Communal space will be managed optimally for the development and maintenance carried out by pesertauni. In Tambora Flats (Rusunawa), spacious units of dwelling cause residents need communal space as a place for them to socialize quickly. Understanding and skills regarding the development and maintenance of independent (participatory) spaces are very much needed to improve the use of space, improve the quality of the environment, as well as improve the skills of low-cost housing residents. The target of PKM this time consists of piloting the construction of recycled concrete communal spaces and participatory communal maintenance rooms. The PKM program this time aims to increase knowledge and understanding of communal spaces and the ability to develop these spaces in a participatory manner. The purpose was made through a demonstration of communal space using concrete materials, concrete residue tests from the FTSP Concrete Laboratory as the main material for making benches and garden boundaries. The pilot participants were RW 11 management, RT 009 management, residents who work as artisans, and other residents of Tambora Rusunawa residents in Kelurahan Angke, Tambora District. Participatory agreement required by residents from the design process to completion. The communication room PKM Team Program provides an insight into the design of a good communal space with facilitators who encourage residents to get in the care of the space